Evaluation of possible approaches to the determination by the method rp hplc natural oils in repellent compositions - L. A. Nosikova; A. N. Kochetov (Тонкие химические технологии)
Considered the possibility of determining the content of natural multicomponent oils in repellent means from insects and rodents. For the analysis of finished products on the basis of Lavandin oil and a blend of essential oils containing as a main component citral, the method RP HPLC with UV detection as an alternative to more expensive options with mass-selective detection. Proposed methods of group content evaluation components of the oils with reference to a specific substance (citral), or without it. For the development and validation of the final analysis it is necessary to apply a differentiated approach in the evaluation of formulations of active substances containing multicomponent natural mixture. Perhaps the correct procedure of the analysis is to identify not only the main component (for example, citral), and minor/s components, the definition of which will more accurately indicate the actual content in the media compositions of active ingredients of disinfectants.